Student Action in Defending the Country Upholding Pancasila Values - Ajeng Maulana Hapsari; Allia Amanda Febri Wahyuningtiyas (Eastasouth Institute, 2023)
Defending the country is essentially the awareness of filial piety to the country and the awareness of sacrificing to defend the country. It covers the best crimes and deeds for the nation and the state. Defending the country is love for the homeland, awareness of the government and state, being convinced of the power of Pancasila, being willing to sacrifice for the nation and state, and having the initial ability to defend the country. This study aims to find out how students take shape in protecting the country by upholding the values of Pancasila. The research method used is a skin method with natural observation, trying to understand and interpret the meaning of an event of human behavior interaction in a particular situation according to the researcher's perspective. The result of this research is that state defense is the attitude and behavior of citizens imbued with their love for the Unitary State of the Republic of Indonesia. State defense awareness in students is implemented when disposing of garbage in the space provided, protection and security for the community is good, religious observance by having carried out and carrying out worship and maintaining the harmony of life among fellow religious people and belief in God Almighty, consciously having cultivated me to be independent someday, and proud in the struggles of the heroes. However, there is a lack of awareness of state defense among students, namely participating in maintaining the security of the campus environment, not representing the campus enough in sports and arts activities.